Organizational Black Hole Phenomenology: Politicization of Education System - Mahdi Mohammadreza'i; Behrouz Rezaeemanesh; Reza Vaezi; Vaghollah Ghorbanizadeh (فرایند مدیریت و توسعه, 2023)
Purpose: The purpose of the current research was to investigate the nature of the black hole of politicization in the Education Ministry of Iran and to identify its causes and outcomes. Methodology: The approach of the research was qualitative, and the strategy used was phenomenology. To collect data from departments and organizations affiliated to the Ministry of Education, semi-structured interviews were performed. For this purpose, interviews were conducted with fifteen experts and education managers, and data coding was done using thematic analysis method. Findings: Findings include the presentation of a structure containing the meaning and concept, factors, effects, and outcomes of the black hole of politicization in the Ministry of Education. The meaning and concept of this phenomenon includes the politicization of human resources management, excessive influence of ideological discourse in the system and contents of education, political interventions in the structure and administrative and educational plans. The factors that create the phenomenon include organizational and contextual factors. The outcomes of the phenomenon are individual, organizational, and environmental. Originality: The present research, contributed to such cases as the country’s education system, development of conceptual realm of politicization, identifying politicization black hole and proposing practical recommendations as well as solutions for eradicating this black hole. Moreover, by identifying the factors (actions and behaviors) of politicization black hole, this study will help the prevention of the occurrence of this phenomenon in future.